An assessment of the psychometric properties of the Chinese version of the Gout Impact Scale. (2nd January 2020) - Pao, Che-Hung; Ko, Yu
Abstract: Objective: To assess the psychometric properties of the Chinese version of the Gout Impact Scale (GIS), a gout-specific HRQoL measure. Methods: This was a single-center, cross-sectional, observational survey of patients with gout recruited from the Taipei Medical University Hospital from November 2017 to April 2018. The respondents were recruited by convenience sampling. The reliability of the Chinese GIS was tested by Cronbach's α coefficient and adjusted using the Spearman–Brown prophecy formula. Content validity was assessed and confirmed by rheumatologists and pharmacists before the administration of the survey. Convergent validity was tested by Spearman correlation analysis to examine the association of the EQ-5D-5L with GIS total and subscale scores. Construct validity of the Chinese GIS was assessed by hypothesis testing. Results: A total of 311 patients were included in the analysis. The majority of these respondents were male (93.2%) with no comorbidities (69.5%) and they had a mean age of 52.9 (±14.2) years. The internal consistency of the Chinese GIS subscales was acceptable to excellent (Cronbach's α = 0.73–0.98) after adjusting to a 10 item scale with the Spearman–Brown prophecy formula. The GIS total and subscale scores were significantly associated with lower EQ-5D-5L scores ([−0.14] – [−0.27], p < .05). In addition, the GIS total and all subscale scores had a significant positive correlation with gout attack severity ( rs = 0.13–0.57, p < .05) and gout attack pain ( rs = 0.17–0.54, p < .01). Moreover, respondents' most recent sUA concentration was associated with both the GIS gout concern overall subscale ( rs = 0.13, p < .05) and the unmet gout treatment need subscale ( rs = 0.18, p < .01). Conclusions: The present study demonstrates that the Chinese version of the GIS shows good internal consistency and association with gout-related characteristics. Future studies may consider using this gout-specific instrument to assess the HRQoL of gout patients in Taiwan.